2020
DOI: 10.1159/000510365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Cold Exposure on Central Aortic Blood Pressure in Patients with CKD

Abstract: <b><i>Objectives:</i></b> Study determined effects of arterial hypertension and impaired kidney function on acute cold exposure induced changes in peripheral and central aortic blood pressure (BP). <b><i>Methods:</i></b> Five-six subjects were divided into 3 groups including 20 hypertensive patients with normal kidney function (AH-non-CKD), 20 patients with hypertension and CKD (AH-CKD) stage 3b–4 and 16 healthy normotensive subjects (C). Baseline BP, central BP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“… 32 And acute cold exposure can lead to a significant increase in arterial blood pressure in patients with or without comorbid CKD. 33 Therefore, avoiding acute cold exposure and enhancing warmth measures in cold exposure are particularly important. Environmental lead exposure increases the risk of CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 And acute cold exposure can lead to a significant increase in arterial blood pressure in patients with or without comorbid CKD. 33 Therefore, avoiding acute cold exposure and enhancing warmth measures in cold exposure are particularly important. Environmental lead exposure increases the risk of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that the association between cold exposure promoting CKD-related hospital visits is stronger than at moderate and high temperatures 32. And acute cold exposure can lead to a significant increase in arterial blood pressure in patients with or without comorbid CKD 33. Therefore, avoiding acute cold exposure and enhancing warmth measures in cold exposure are particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…And they suggested to follow the out-of-office blood pressure of these patients to further understand the seasonal change ( 72 ). On the opposite, a recent study from Poland evaluated the central blood pressure of 56 patients exposed to cold (10 minutes of -10°C) and found out that the central aortic pressure was higher in hypertensive patients with CKD than in normotensive patients ( 73 ). When it comes to hemodialysis patients and seasonal variation, two cohorts from Taiwan showed that hemodialysis patients may have an increase in fluid accumulation during the cold season if they had a lower fractional weight loss ( 74 , 75 ).…”
Section: The Weather and The Kidneymentioning
confidence: 99%